Scenario-Based Evaluation of Economic Feasibility and Risk in City Gas Networks: A Case Study From East Java, Indonesia - Deddy Tricahyo Utomo; Cindy Dianita (Testing Center for Oil and Gas LEMIGAS, 2025)
This study aims to evaluate the economic feasibility and develop optimization scenarios for a natural gas distribution network intended for household use. The case study employs existing gas pricing and consumption data from East Java Province to support realistic economic modeling. The analysis examines how three important factors the number of customers, the price of gas, and how much gas is used affect key economic measures: net present value (NPV), internal rate of return (IRR), payback period (PP), and benefit-cost ratio (BCR). The research methodology includes secondary data collection, simulation of six different scenarios, and sensitivity analysis to examine the critical factors influencing project viability. Simulation results indicate that the scenario assuming a 25% increase in both gas selling price and gas consumption yields the most favorable economic performance, with an IRR of 14.21% and a payback period of less than seven years. The novelty of this study lies in its integrated use of scenario-based economic modeling, sensitivity analysis, and international benchmarking with comparable industries. Unlike conventional feasibility studies that focus solely on regional expansion, this research underscores the strategic role of pricing and consumption patterns as key determinants of financial sustainability in residential gas networks. The findings from the sensitivity analysis reveal that gas selling price has the most significant impact on economic performance, followed by gas consumption rate. These insights reinforce the importance of pricing adjustments and consumption optimization in enhancing the financial and operational sustainability of natural gas distribution networks. The study concludes with strategic recommendations for operators and policymakers to advance efficient and resilient gas-based energy infrastructure.